Adsorption of phenol by MMT-CTAB and WPT-CTAB: Equilibrium, kinetic, and thermodynamic study. (18th August 2018) - Ceylan, Zeynep; Mustafaoglu, Damla; Malkoc, Emine
ABSTRACT: In this study, the phenol adsorption capacity of cetyltrimethylammonium bromide modified clays (MMT-CTAB) and cetyltrimethylammonium bromide modified pulp tea (WPT-CTAB) were studied. In batch adsorption experiments performed with MMT-CTAB, the effects of parameters such contact time, phenol concentration, pH of solution and adsorbent dosage were investigated. The effect of temperature on phenol adsorption onto MMT-CTAB and WPT-CTAB was examined; equilibrium and thermodynamic studies were completed. The highest phenol removal was found at pH 4.0 for MMT-CTAB and WPT-CTAB. To analyze the kinetics of phenol adsorption onto MMT-CTAB, the pseudo first-order and pseudo second-order kinetic models were applied. The kinetic data fitted better to the pseudo second-order model than the pseudo first-order kinetic model for MMT-CTAB. The characterization of adsorbents in phenol adsorption was clarified with the FTIR technique. Thermodynamic parameters such as ΔH°, ΔS° and ΔG° were calculated for each adsorption process. The adsorption process was found to be exothermic and spontaneous for phenol adsorption by MMT-CTAB and WPT-CTAB. The results were analyzed with the Langmuir, Freundlich, Temkin and Harkins–Jura equations using linearized correlation coefficients at different temperatures. The Langmuir equation was found to best represent the equilibrium data for phenol adsorption onto MMT-CTAB and WPT-CTAB.